DIKSI, GAYA BAHASA, DAN KATA KONKRET DALAM LIRIK LAGU KARYA NINOMIYA KAZUNARI - , NOOR SAIDAH, Wiastiningsih, S.S., M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This graduation paper explores the usage of diction, style of language, and concrete word in the Ninomiya Kazunariâs lyrics. Lyrics of the song have the same characteristic as poem. A poem consists of the nature of poetry (inner structure) and the method of poetry (physical structure). Diction, style of language, and concrete word are the elements of method of poetry. Diction is the chosen words that are used by poets to deliver the meaning, concrete word means the words that are used by poet to make the meaning of his or her poetry real and concrete, and style of language focuses on conveying the meaning of poetry by poets in indirectness way. With the analysis of diction, style of language, and concrete word in the lyrics of the song, the writer is able to understand the meaning of lyrics created by Ninomiya Kazunari. The writer also analyzes Riffaterreâs indirectness of expression in the Ninomiya Kazunariâs works to find out the typical style of Ninomiya Kazunari in delivering the meanings of his works. Niji, Gimmick Game, and 1992*4##111 are the data of this research. Ninomiya Kazunariâs typical styles in delivering of the three are: a dialogue or conversation of two characters, immense katakana, an unusual way to read some kanji, and unfamiliar way to write the lyrics, i. e. only provide a few repetation. Concerning the meaning, three of them have the different themes but have a typical appeal in conveying the meaning. The meaning of Niji is about the memories of a spouse when they were still dating. The meaning of Gimmick Game is about a couple that lied and betrayed each other, while the meaning of 1992*4##111 is about saying a gratitude through a code.